Fumi - Sim, Peng Hui (2014)
Singapore, a fast ageing population country; has the third largest potential eldercare market among the Asia-Pacific countries. Beside the fact of ageing, unbalance lifestyle of Singaporean has exposed those non-communicable diseases to them where they can be avoided or delay by doing regular exercise. But people giving excuses of not having enough time for exercise, bad weather and some prefer staying in their comfort zone; thus, having gym equipment at home will be a better choice. While for the elderly, gym equipment are usually too complex to operate and some are not ergonomically design for them.